Reading Aloud and Solving Simple Arithmetic Calculation Intervention (Learning Therapy) Improves Inhibition, Verbal Episodic Memory, Focus Attention and Processing Speed in Healthy Elderly People: Evidence from a Randomized Controlled Trial - Nouchi, Rui; Taki, Yasuyuki; Takeuchi, Hikaru; Nozawa, Takayuki; Sekiguchi, Atsushi; Kawashima, Ryuta (Frontiers in Human Neuroscience, 2016)
Background Previous reports have described that simple cognitive training using reading aloud and solving simple arithmetic calculations, so-called “learning therapy”, can improve executive functions and processing speed in the older adults. Nevertheless, it is not well-known whether learning therapy improve a wide range of cognitive functions or not. We investigated the beneficial effects of learning therapy on various cognitive functions in healthy older adults. Methods We used a single-blinded intervention with two groups (learning therapy group: LT and waiting list control group: WL). Sixty-four elderly were randomly assigned to LT or WL. In LT, participants performed reading Japanese aloud and solving simple calculations training tasks for 6 months. WL did not participate in the intervention. We measured several cognitive functions before and after 6 months intervention periods. Results Compared to WL, results revealed that LT improved inhibition performance in executive functions (Stroop: LT (Mean = 3.88) vs. WL (Mean = 1.22), adjusted p =.013 and reverse Stroop LT (Mean = 3.22) vs. WL (Mean = 1.59), adjusted p =.015), verbal episodic memory (logical memory: LT (Mean = 4.59) vs. WL (Mean = 2.47), adjusted p =.015), focus attention(D-CAT: LT (Mean = 2.09) vs. WL (Mean = -0.59), adjusted p =.010) and processing speed compared to the waiting list control group (digit symbol coding: LT (Mean = 5.00) vs. WL (Mean = 1.13), adjusted p =.015 and symbol search: LT (Mean = 3.47) vs. WL (Mean = 1.81), adjusted p =.014). Discussion This RCT can showed the benefit of learning therapy on inhibition of executive functions, verbal episodic memory, focus attention, and processing speed in healthy elderly people. Our results were discussed under overlapping hypothesis. Trial registration “This trial was registered in The University Hospital Medical Information Network Clinical Trials Registry (UMIN000006998).”